An integrative action research (IAR) on improving the collaboration and inclusion of a diverse workforce unit - Gracilla, Remedios Irene C. (Animo Repository, 2022)
As we are moving in this globalization era where businesses and organizations continue to expand their operation on an international scale. It makes the workplace more diverse than ever. Workforce diversity brought various reflections linking its importance in building an effective organization and thus requires appropriate and strategic management. This paper aims to address the gaps and provide opportunities to improve the collaboration and inclusion of a diverse workforce in the context of one of the units of a well-known global financial service. Through action research tools, methods of inquiries alongside Lewin’s Planned Change Model, and collective ideas and collaboration it provides an inclusive approach to managing the change by creating a working group for the unit - this working group is founded on the pillars of process improvement, learning & development, events, and rewards & recognition assembly. While the theory of collaboration, Gartner Inclusion Index and Relational Model of diversity have been a vital contribution to improving and evaluating collaboration and inclusion while sustaining and at the same time integrating its purpose on a wider departmental & organizational agenda. Thus, this insider action research marks the ability of working group concept realized for a diverse workforce is integral in improving collaboration and inclusion which resulted in coming up a conceptual framework of diversity management used within this action research initiative which can eventually offer significant insight to the field of diversity management.